2019
DOI: 10.1186/s12879-019-3878-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and managements of severe hand, foot and mouth disease caused by enterovirus A71 and coxsackievirus A16 in Shanghai, China

Abstract: Background Hand, foot and mouth disease (HFMD) is a transmissible infectious disease caused by human enteroviruses (EV). Here, we described features of children with severe HFMD caused by EV-A71 or coxsackievirus A16 (CV-A16) in Shanghai, China. Methods Severe EV-A71 or CV-A16 caused HFMD children admitted to the Xinhua Hospital from January 2014 and December 2016, were recruited retrospectively to the study. Symptoms and findings at the time of hospitalization, laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…Among the newborns with HFMD complicated with encephalitis in our hospital, most of them were infected with HFMD common virus, a few were infected with CA16 and no EV71 infection, and most of them developed into severe cases because of EV71 infection, which may be one of the reasons for the good prognosis of most of the newborns with HFMD in our hospital. In our hospital, the vast majority of newborns have fever, which is consistent with foreign reports ( 11 ). The rash is not specific and atypical, usually manifesting as punctate rash or macular papule.…”
Section: Discussionsupporting
confidence: 92%
“…Among the newborns with HFMD complicated with encephalitis in our hospital, most of them were infected with HFMD common virus, a few were infected with CA16 and no EV71 infection, and most of them developed into severe cases because of EV71 infection, which may be one of the reasons for the good prognosis of most of the newborns with HFMD in our hospital. In our hospital, the vast majority of newborns have fever, which is consistent with foreign reports ( 11 ). The rash is not specific and atypical, usually manifesting as punctate rash or macular papule.…”
Section: Discussionsupporting
confidence: 92%
“…This result suggests that CD55 suppresses T cell immunity in vivo. The downregulation of sCD55 in the patients with EV71 infection in our study, especially severe cases, may also be associated with hyperactive T cell immunity, as previous studies have reported that EV71 infection causes increases in IFN‐γ and IL‐2 36,37 …”
Section: Discussionsupporting
confidence: 68%
“…Previous studies had found out that aseptic meningitis could be caused by EV in children or infants and emphasized the importance of CSF virus nucleic acid detection for diagnosis. [ 15 , 23 ] Meanwhile data on neonates were still limited. Only a few studies involved neonates, which had also shown that EV was an important pathogen in neonatal viral meningitis.…”
Section: Discussionmentioning
confidence: 99%